Sports selection system in triathlon - Volodymyr Vodlozerov (Kharkiv State Academy of Physical Culture, 2016)
Purpose: to analyze the contents of the main stages of sports selection of triathletes. Material & Methods: study and generalization of special literature on the issue of sports selection in continuous triathlon, analysis of triathletes selection based on normative documents. Results: there were reviewed the particularities of sports selection of triathletes on each of its main stages and the role of heredity as a necessary condition for practicing sports for endurance, and also there was shown the procedure of calculation of rating points. Conclusions: sports selection plays a key role in the admission of pupils to the departments of triathlon in sports schools as well as in the formation of picked teams of all levels for participation in competitions on continuous triathlon.